Late ANC initiation and factors associated with sub-optimal uptake of sulphadoxinepyrimethamine in pregnancy: a preliminary study in Cape Coast Metropolis, Ghana - Amoako, B.K.; Anto, F. (BMC Pregnancy and Childbirth, 2021)
Background: Malaria infection during pregnancy is of public health importance as it poses risk to the pregnant woman, her foetus and the newborn child. Intermittent preventive treatment during pregnancy using sulphadoxine-pyrimethamine is one way of reducing the effect of the disease on pregnancy outcomes. The study determined factors associated with uptake of sulphadoxine-pyrimethamine during pregnancy in the Cape Coast Metropolis of Ghana. Methods: A health facility-based cross-sectional study involving pregnant women of ≥36 weeks gestation visiting antenatal clinics in three selected health facilities in the Cape Coast Metropolis was conducted. Participants were consecutively recruited using a structured questionnaire over a 6-week period from May to June, 2018. Descriptive statistics was used to summarize the data whilst Pearson’s chi-square/Fisher exact test was performed to determine associations and logistic regression done to determine the strength of the associations. Results: A total of 212 pregnant women participated in the study. Formal education, initiating ANC early, taking first dose of SP during second trimester, not experiencing side effects of SP, having knowledge about schedule for taking SP and making ≥4 ANC visits were factors associated with uptake of ≥3 doses of IPTp-SP. Logistic regression analysis revealed that, mothers who made ≥4 ANC visits were 53.77 times more likely to take ≥3 doses of SP compared with those who made < 4 ANC visits (p < 0.001). Those who initiated ANC during the first trimester were 3.60 times more likely to receive ≥5 doses compared with those who initiated ANC during the second or third trimester (p = 0.022). Making ≥8 ANC visits did not increase the chances of taking ≥5 doses of SP. Conclusion: Health promotion programmes targeting mothers with no formal education could increase their awareness about the importance of ANC services including uptake of IPTp-SP.
Research Article
Keywords: Malaria; Pregnant woman; Sulphadoxine-Pyrimethamine; IPTp-SP; Antenatal care